2016
DOI: 10.1007/s11368-016-1372-y
|View full text |Cite
|
Sign up to set email alerts
|

Diel turbidity cycles in a headwater stream: evidence of nocturnal bioturbation?

Abstract: Purpose A small number of recent studies have linked daily cycles in stream turbidity to nocturnal bioturbation by aquatic fauna, principally crayfish, and demonstrated this process can significantly impact upon water quality under baseflow conditions. Adding to this limited body of research, we use highresolution water quality monitoring data to investigate evidence of diel turbidity cycles in a lowland, headwater stream with a known signal crayfish (Pacifastacus leniusculus) population and explore a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
(37 reference statements)
2
16
0
1
Order By: Relevance
“…This yielded a near-continuous record of river turbidity (NTU) for a period of 58 months prior to wetland installation (October 2011 -August 2016) and 16 months after installation (November 2016-February 2018. These turbidity measurements were then calibrated against suspended particulate matter concentrations (SPM) by ordinary least squares regression using between 93 and 299 river water grab samples previously collected at each site under a range of highand low-flow conditions between May 2012 and March 2014 (Figure S1) (Cooper et al, 2016).…”
Section: Riverine Monitoring: High-resolutionmentioning
confidence: 99%
“…This yielded a near-continuous record of river turbidity (NTU) for a period of 58 months prior to wetland installation (October 2011 -August 2016) and 16 months after installation (November 2016-February 2018. These turbidity measurements were then calibrated against suspended particulate matter concentrations (SPM) by ordinary least squares regression using between 93 and 299 river water grab samples previously collected at each site under a range of highand low-flow conditions between May 2012 and March 2014 (Figure S1) (Cooper et al, 2016).…”
Section: Riverine Monitoring: High-resolutionmentioning
confidence: 99%
“…Although unexpected, observations of night‐time increases in particle concentration in riverine systems are not unique and have been attributed to nocturnal biological activity, for example, night‐time feeding or foraging behaviour by fish or crayfish. Gillain (); Loperfido, Just, Papanicolaou, and Schnoor (); and Harvey et al (), Rice, Johnson, Extence, Reeds, and Longstaff (), and Cooper, Outram, and Hiscock () observed diel turbidity fluctuations in streams in Georgia, Iowa, and the United Kingdom, respectively. Gillain () explored instrumentation effects, sediment transport, and biological activity as potential sources of night‐time turbidity increases and concluded that biological activity was the likely cause of diel turbidity cycling.…”
Section: Resultsmentioning
confidence: 94%
“…ii) Examination of the dominant facets of turbidity and discharge that influence sediment ingress using correlation matrices and the development of linear regression models using the principal component sample scores. (Harvey et al, 2014;Rice et al, 2014;Cooper et al, 2016) although this was not an explicit consideration in the research reported here.…”
Section: Principal Component Analysis a Well-established Multivariatmentioning
confidence: 92%